The Development of Students’ Linguistic Competence in the Course of Education in the Humanities - Карина Юрьевна Колесина (Российский психологический журнал, 2015)
The article is devoted to one of the key problems of modern system of University education, namely education in the Humanities, i. e. identiWcation of personal meaning in education and personal meaning of the subjects under study.